(untitled) (Scientific World, 2021)
Mistletoes are being used for food or beverage and for variety of medicinal purposes. In Nepal, mistletoes are traditionally used as fodder and as remedy to cure various ailments. In this study, methnolic extracts of seven common mistletoe species (Helixanthera ligustrina, Macrosolen cochinchinensis, Scurrula elata, S. parasitica, Viscum album, V. articulatum and V. liquidambaricola) were analyzed for their phytochemical constituents and antioxidant potential. The total flavonoid content (TFC) and total phenol content (TPC) were quantitatively determined by aluminum chloride colorimetric and folin-cioalteau reagent methods, respectively. The TFC was found highest for V. album (31.5 ± 2.3 mg QE/g) and lowest for M. cochinchinensis (24.9 ± 2.3 mg QE/g). Similarly, highest total phenolic content was found in S. parasitica (32.9 ± 2.5 mg GAE/g) and lowest in V. album (20.6 ± 2.1 mg GAE/g). The antioxidant activity measured by DPPH radical scavenging assay was found best for S. parasitica (with lowest IC₅₀ value; 26.0 ± 0.7 µg/ml) among the studied mistletoes. Overall analysis provides scientific evidence in favor of indigenous use of these mistletoes as a source of fodder, food and for medicinal purposes